Simulation of Fluid Flow During Direct Synthesis of H2O2 in a Microstructured Membrane Reactor. Issue 5 (19th March 2021) - Trinkies, Laura L.; Düll, Andrea; Deschner, Benedikt J.; Stroh, Alexander; Kraut, Manfred; Dittmeyer, Roland
Abstract: A microstructured membrane reactor has been developed to overcome the safety and productivity challenge of the direct synthesis of hydrogen peroxide. A single membrane is employed for separate, continuous dosage of the gaseous reactants hydrogen and oxygen to the solid catalyst present in the aqueous solvent. Using a custom OpenFOAM® model, the impact of catalyst‐coated static mixers with different mixer geometries is studied. It is demonstrated that the custom fluid guiding elements outperform the investigated commercial static mixer under the flow conditions relevant to this application. Abstract : A CFD model of a microstructured membrane reactor with integrated fluid guiding elements for the direct synthesis of hydrogen peroxide is developed and implemented in the form of a customized solver in OpenFOAM®. To optimize the process window of the operational and design parameters, the impact of the insert's geometry on the reactor's performance is investigated.